TATA KELOLA DAN PELAYANAN ADMINISTRASI - Khalil, Zakki Fuad; Fitri, Azizah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2019)
This study aims to discuss governance and administrative services in government, where the main aspects in the process of public service which is the good and bad services in an institution, can be seen from administrative governance. This research is a field research at the Central Aceh District Secretariat. The results of the study found that governance and administrative services provided were guided by the principles of accountability, participation, responsiveness, consensus, effectiveness and efficiency. While in practice the administration of administrative services in the Central Aceh District Secretariat is still not maximal toward the role played in implementing a good governance system. So it has an impact on the bureaucratic system and the service process that is not in accordance with standard operating procedures.